Molecular phylogeny of the subfamily Stevardiinae Gill, 1858 (Characiformes: Characidae): classification and the evolution of reproductive traits. (December 2015) - Thomaz, Andréa; Arcila, Dahiana; Ortí, Guillermo; Malabarba, Luiz
Abstract Background The subfamily Stevardiinae is a diverse and widely distributed clade of freshwater fishes from South and Central America, commonly known as "tetras" (Characidae). The group was named "clade A" when first proposed as a monophyletic unit of Characidae and later designated as a subfamily. Stevardiinae includes 48 genera and around 310 valid species with many species presenting inseminating reproductive strategy. No global hypothesis of relationships is available for this group and currently many genera are listed asincertae sedis or are suspected to be non-monophyletic. Results We present a molecular phylogeny with the largest number of stevardiine species analyzed so far, including 355 samples representing 153 putative species distributed in 32 genera, to test the group's monophyly and internal relationships. The phylogeny was inferred using DNA sequence data from seven gene fragments (mtDNA:12S, 16S andCOI ; nuclear:RAG1, RAG2, MYH6 andPTR ). The results support the Stevardiinae as a monophyletic group and a detailed hypothesis of the internal relationships for this subfamily. Conclusions A revised classification based on the molecular phylogeny is proposed that includes seven tribes and also defines monophyletic genera, including a resurrected genusEretmobrycon, and new definitions forDiapoma, Hemibrycon, Bryconamericus sensu stricto, andKnodus sensu stricto, placing some small genera as junior synonyms. Inseminating species are distributed in several clades suggesting that reproductive strategy is evolutionarily labile in this group of fishes.